Perspectives of febrile convulsions among parents: a local cross-sectional study - Latifah Abdulrahim Alhashim; Ossama Mohammed Zakaria; Muneera Adel Alrubayii; Asma Salah Alkhofi; Sarah Khalid Alateeq; Maitha Khalid Almaghlouth; Reema Mohammed Almulla; Ahmed Abdulrahman Al Abdulqader; Latifah Abdullah Almulhium; Abdulrahman Ahmad Alnaim (SpringerOpen, 2022)
Abstract Background Globally, febrile convulsions (FC) constitute a respected prevalence scale among pediatric population. This usually induces a high parental anxiety. Aim To investigate the local community diversity of perception as regards FC. Method A cross-sectional anonymous Arabic questionnaire-based study took place targeting the Saudi community. The study included parents with at least a child who underwent FC. Excluded, were those who have children with convulsions due to other causes rather than FC. Results Eight hundred participants have fulfilled the study inclusion criteria. Majority of them (84%) were mothers. While 10.9% had only one child diagnosed with FC. Participants believed that FC may induce brain damage (41.4%). Others expressed FC attacks to be life-threatening events (52.9%). They were convinced that FC is not related to epilepsy (40.2%). However, a respected percentage of participants denoted the importance of using oral protective devices during the attacks (41.4%). Overall, most study population (84%) had poor perception of the different aspects of FC. Conclusion Social perception of FC problems may be significantly related to the educational level and profession of the parents. The majority of the study subjects have poor perception as regards FC. Therefore, holistic socially oriented educational programs are needed to orient the population about the problem. They may be implemented via various approaches.